Hemodynamic response to Sevoflurane and Propofol induction: a comparative study - Rawal, Prabhat; Bajracharya, Uday (Journal of Society of Anesthesiologists of Nepal, 2015)
Background: Induction of anesthesia is a critical event and hemodynamic stability is an important factor during this period. Propofol is a commonly used intravenous anesthetic and Sevoflurane is a newly introduced inhalational anesthetic in the context of a developing country. This study compared the hemodynamics on induction of anesthesia with Propofol and Sevoflurane. Methods: A total of 108 American Society of Anesthesiologists physical status I patients undergoing elective surgical procedures under general anesthesia were randomized into two groups. Group ‘P’ patients were induced with intravenous 1% Propofol and Group ‘S’ patients were induced with inhalation of 8% Sevoflurane. Mean arterial pressures and heart rates were recorded at baseline, before induction, during induction and at 1, 3 and 5 minutes after induction of anesthesia before endotracheal intubation. Results: The two groups were comparable with respect to demographics and baseline hemodynamic parameters. There was a significant decrease in mean arterial pressure and heart rate from pre-induction values within both groups during and after induction. The reduction in mean arterial pressure was significantly more in Propofol group transiently during induction. The reduction in heart rate was significantly more in Sevoflurane group at 1, 3 and 5 minutes after induction (P < 0.05). Conclusion: Induction of anesthesia with Propofol demonstrated a greater decrease in mean arterial pressure whereas induction with Sevoflurane was associated with greater reduction in heart rate. Journal of Society of Anesthesiologists of Nepal 2015; 2(1): 2-7